Studi Literatur Analisis Keandalan Komponen Industri dan Penerbangan - Sherly Hutri Permatasari; Hadi Pranoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Abstract: This study aims to map the analysis methodologies and the main triggers of technical component failure in the mechanical systems of the manufacturing and aviation industries. The method used is a Systematic Literature Review focusing on analysis parameters from Weibull distribution, Failure Mode and Effects Analysis (FMEA), Fault Tree Analysis (FTA), and Reliability-Centered Maintenance (RCM). The results of the study indicate that the majority of critical devices, especially hydraulic systems and actuators, have entered the wear-out phase. This is statistically proven through Weibull distribution parameters that are consistently above one (β > 1) with a contrasting priority where aviation prioritizes regulatory safety (MEL) while manufacturing focuses on cost efficiency. In conclusion, determining an accurate Mean Time to Failure (MTTF) is key to maintaining system integrity while reducing operational expenses in both sectors. Keywords: Component Reliability, Mean Time to Failure, Root Cause Analysis, Systematic Literature Review, Weibull Distribution